PENGEMBANGAN WADAH KERUKUNAN DAN KETAHANAN MASYARAKAT KECAMATAN PALU SELATAN KOTA PALU PROVINSI SULAWESI TENGAH (Harmoni, 2012)
Dynamic of religious life in south Palu is  normal and condusive. It is supported by some factors, that are conditioned among the people and it might be a model for other provinces. Actually the form of harmonious life has not been productive  in terms of interreligion cooperation. Some  most factors in creation of such good life are  resilience developing for individual, family and interreligious community. This study is approached by qualitative research.
Keywords: Heterogen; Konflik; Kerukunan; heterogeniy; conflict; harmony; religious community